Recurrences of atrial fibrillation in patients with heart failure without reduced ejection fraction: a role for CA125. (14th October 2021) - Perez Rivera, J A; Merino-Merino, A; Saez-Maleta, R; Gundin-Menendez, S
Abstract: Background: Atrial fibrillation (AF) and heart failure (HF) without reduced ejection fraction often occur together, and their combination is associated with increased morbidity and mortality compared with each disorder alone. Sinus rhythm maintenance seems to be beneficial but challenging in these patients. Purpose: We studied the possible value of CA125 to predict recurrences in patients with persistent AF and HF without reduced ejection fraction who underwent electrical cardioversion (ECV). Methods: We designed a prospective cohort study by consecutively including all the patients who underwent ECV in our hospital with symptomatic persistent non-valvular AF and a concomitant diagnosis of HF without reduced ejection fraction. We excluded patients with clinical instability or ejection fraction <40%. We defined HF as the presence of diastolic dysfunction in echo (left atrium indexed volume >34 ml/m 2 or e/e' >8) or ejection fraction between 40 and 50%. We followed-up them during 6 months for detecting AF recurrences with an ECG-Holter 3 months after ECV and an ECG at 6th month. We considered a recurrence as any AF documentation in ECG or ECG-Holter after the ECV. A peripheral blood sample was extracted just before ECV and CA125 was determined. Kaplan-Meyer analysis was used to study the possible relationship between CA125 plasmatic levels, dichotomized according to the median value, and AF recurrence. Results: We included 95 patients with a medium age of 64±9 years old. Of them, 31 (32.6%) were women, 14 (14.7%) had diabetes and 56 (58.9%) hypertension. The medium ejection fraction was 58.14±10.27% and the median CA125 was 10.98±8.97 U/ml. We detected 54 (57.4%) recurrences in 6 months. In patients with AF recurrences, CA125 values were higher than in patients who maintained sinus rhythm (19.28±29.11 U/ml vs. 14.98±17.02 U/ml). CA125 was significantly related with AF recurrences (log-rank 5.37; p=0.021). Conclusions: In our sample of patients with persistent AF and HF without reduced ejection fraction, CA125 plasmatic levels are related with AF recurrences after ECV. CA125 has been associated with the clinical severity of HF and the symptoms and signs of fluid congestion. This probably means more ventricular and atrial myocardial damage that might predispose to AF. Sinus rhythm maintenance is specially challenging in patients with HF so those with higher levels of CA125 probably need a closer surveillance and a more aggressive rhythm control. Funding Acknowledgement: Type of funding sources: None.